Eco-Compensation Analyses for Drinking Water Reserves Based on Integrated Ecosystem Health Assessment - Xu, Meng; Li, Chunhui; Shen, Nan; Cai, Yanpeng; Wang, Xuan (Journal of Environmental Accounting and Management, 2026)
Eco-compensation is used to deal with varying eco-environmental issues associated with possible resources transfer. It aims to translate nonmarket values of any environmental services into real financial incentives for the concerned stakeholders. In this paper, an integrated ecocompensation approach was proposed based on ecosystem health assessment through incorporating the assessment results into the assessment criteria. Compensation ranges were identified and taken as the references to formulate short-, middle- and long-term eco-compensation targets. Then, Xin’an Drinking Water Reserve in China was used as a studying case, the calculated results of compensation amounts were (63.1, 122.9); (128.4, 192.5) and (195.2, 202.1) million RMB Yuan, respectively, under short-, middle- and long-terms. Through comparing results with those of the previous approaches, the developed approach have the following advantages: a) with the aim of ecological reclamation, the results based on the integrated approach could reflect the real costs needed for ecological recovery of the previously contaminated reserves; b) comparatively flexible since it can adjust its eco-compensation targets flexibly according to the practical situation for ecosystem recovery levels; and c) the value intervals could indicate the degrees of compensation inputs on the overall ecological recovery, thus the possible compensation targets could be established accordingly.